Modeling Crucial Road Environment Risk Factor for Developing Asian Countries Using Principal Component Analysis - Intan Suhana, Mohd Razelan; Hussain, H.; Law, T. H.; Ahmad Farhan, Md. Shokeri (2015)
Traffic accidents in developing countries imposed serious effect especially in terms of its economic turnover on medical supplies and vehicles parts (Bener, A., et al. 2003). Bener, A., et al. (2003) who had done extensive works in proposing a strategy to improve road safety in developing countries concluded that Malaysia is also one of the most prominent countries in this issue. He summarized that by looking at the motorization levels and fatality rates for various countries within 1988 – 1998, Malaysia has reported to have about 1111.0 vehicles / 10,000 persons with 2.43 fatalities were recorded for every 10,000 persons. As such, this study aims to investigate crucial road environment factors for Asian developing countries by taking Malaysia Federal Road network as study area. Fourteen road environment attributes were selected based on specific criteria with an aim to improve the overall environment condition of the road. Crash data were supplied by Malaysian Royal Police Force (PDRM) and the rest of the data were mainly collected using video-logs and on-site measurement methods. Three stretches of roads comprises of 315.5 km of federal roads were selected as study areas. A test vehicle attached with video-camera was driven along this road where the road environments were recorded. By employing principal component analysis, crucial road environment factors as well as specific attributes that constantly contributed to safety problem of this road were identified. Four road environment factors namely roadway, roadside, road infrastructure and road operational environment have collectively been identified as the most crucial road environment factors for federal roads. Identifications of these factors are very useful since it would be a better reference in identifications of risky environment factors that need urgent treatment.